Analisis Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Caffe Ayang Beib Steak Masa Pandemi Covid-19 - Wati, Asna; Daud, Syahril (CV. Lafadz Jaya, 2022)
The purpose of this study was to determine how the level of consumer satisfaction with the services provided by Caffe Ayang Beib Steak. This research uses quantitative methods. In this study, data were collected using a questionnaire from 100 respondents, where the respondents were consumers of Caffe Ayang Beib Steak. The analytical tools used are Level of Conformity Analysis and Cartesian Diagram Analysis. Based on the results of the study, it can be concluded that the result of the highest average level of conformity is 79.35%, where there are still 7 attributes that are below the average level of conformity. The calculation result of Importance-Performance Analysis is known that the average service quality is 3.14 and the average level of customer satisfaction is 4.58. This shows that 3.14 < 4.58 which means that the quality of service provided by Caffe Ayang Beib Steak during the covid-19 pandemic has not fully satisfied consumers. Meanwhile, the results of the Cartesian Diagram measurement show that there are 4 attributes in quadrant A that must be prioritized by Caffe Ayang Beib Steak. Based on the results of the level of conformity approach, the importance-performance analysis table, and the Cartesian diagram, it can be concluded that the quality of service provided has not been able to meet consumer satisfaction at Caffe Ayang Beib Steak.